NATURAL DRINK âCARICA PAPAYA LINNAEUSâ SOLUSI MASYARAKAT SEHAT - Istiana, Ika; V., Vitasari; Munib, Abdul (Program Kreativitas Mahasiswa - Pengabdian Kepada Masyarakat, 2013)
Sendang is a village that located on the western part of Pacitan Regency. Majority of its society work as a farmer who able to produce papaya in big amaunt. But, the existence of those papayas are not followed by maximal utilization. So, team of PKM-M has done the innovation to make instant drink powder from extract of papaya leave. The purposes of that event, such as to maximize utilization of papaya, to drilled and accompany the society to make healthy drink, build the central of Natural Drink âCarica papaya Linnaeusâ and to decrease the economic difficulty of Sendang society. The conclusion, such as: the prosperity of Sendang society is increased in economy, skill, and health side; maximize utilization of papaya leaves; and create the new open jobs.